1999
DOI: 10.1046/j.1365-2958.1999.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar proteins and type III‐exported virulence factors are the predominant proteins secreted into the culture media of Salmonella typhimurium

Abstract: SummaryWe analysed all major proteins secreted into culture media from Salmonella typhimurium. Proteins in culture supernatants were collected by trichloroacetic acid precipitation, separated in SDS±polyacrylamide gels and analysed by amino acid sequencing. Wildtype strain SJW1103 cells typically gave rise to nine bands in SDS gels: 89, 67, 58, 52, 50, 42, 40, 35 and (sometimes) 28 kDa. A search of the sequences in the available databases revealed that they were either agellar proteins or virulence factors. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
97
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 54 publications
10
97
0
4
Order By: Relevance
“…When grown in culture, S. typhimurium secretes a number of proteins into the culture supernatant (17,18). To determine the role of the individual proteins encoded by the prgHIJK operon in type III secretion, in-frame deletions of each individual gene within the operon were created by allelic exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When grown in culture, S. typhimurium secretes a number of proteins into the culture supernatant (17,18). To determine the role of the individual proteins encoded by the prgHIJK operon in type III secretion, in-frame deletions of each individual gene within the operon were created by allelic exchange.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike PrgH, PrgK, and InvG, which are all membrane-associated proteins, PrgI and PrgJ are secreted into the culture supernatant. Secretion of PrgI and PrgJ may be analogous to the secretion into the culture supernatant of more distal components of the flagellar hook and basal body during flagellar assembly (18). Secretion of PrgJ, and most likely PrgI, requires prgH and prgK, suggesting that assembly of the multiprotein NC occur through ordered secretion, polymerization, and assembly, analogous to flagellar morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that flagellin is secreted into the medium by the flagella secretory apparatus during flagella biosynthesis, in amounts sufficient to cause a proinflammatory immune response. [39][40] Other reports speculated that monomeric or oligomeric flagellin could be also released by the action of proteolytic enzymes, bile salts, or surfactants present in mucosal sites. 41 Moreover, evidence for the release of proinflammatory flagellin monomers in vivo was recently reported by Subramanian and Qadri 42 , who showed that not only the interaction of Salmonella and intestinal epithelial cells promoted monomeric flagellin release but also that this flagellin was not derived from shearing or depolymerization of flagella present on the surface of the bacterium but instead was newly synthesized and secreted after bacterial sensing of host-produced lysophospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high Ab titer against P. aeruginosa flagellin and elevated levels of active NE (up to 20 M in CF sputum) have been detected in CF patients (43,44). Separate studies have also documented the secretion of flagellin by bacteria and NE release from neutrophils in the course of infections (45)(46)(47). In accordance, we detected active NE and different forms of flagellin (intact, complex, and degraded) in mouse lungs in our pneumonia model with P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%